RELIGIOUS EDUCATION MODEL FOR CHILDREN AGE OF PRE SCHOOL IN FAMILY MELAYU SAMBAS - Adnan Mahdi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article focuses on the model of preschool education of preschool-aged children in Sambas Malay family. The purpose of this study was to find the model of preschool education of preschool children in Sambas Malay. The research was conducted in Sambas District, West Kalimantan Province. An in-depth study is directed to aspects of preschool educational goals, preschool educational programs, preschool education process, and evaluation of preschool education. This research is designed with a qualitative approach using penology method. The result of analysis shows that 1) The purpose of religious education of preschool children in Sambas Malay family there are three kinds, namely ideal goal, intermediate goal, and immediate goal; 2) Preschool program of preschool education in Sambas Malay family there are three aspects, namely: Aqidah, worship, and morals; 3) The process of religious education of preschoolers in Sambas Malay family is seen from three aspects, namely method, learning source, and time used to educate children. The method used by parents there is three kinds, namely demonstration, point of pronunciation, and show behavior. Learning resources used include Picture storybook, Iqra ', prayer book, al-Qurân, pictures, posters, mobile phones, televisions, laptops, VCDs, and children's toys. While the time spent educating children is all of the spare time that parents have, especially after Maghrib prayers and at bedtime; and 4) Evaluation of religious education used by Sambas Malay parents in educating preschool children is direct evaluation and indirect evaluation.